Valuation of M&A A Case Study: BenQ’s Acquisition of Siemens Mobile Device Division - Chen, Shu-Ling (2010)
In order to retain or upgrade core competence and sustainability, companies seek for global expansion and conglomeration. Consequently, mergers and acquisition (M&A) has become the most highly possible route for enterprises to pursue future growth in the fast way. Although the historical record shows a higher failure rate, the M&A waves do not appear to exhibit a declining trend in past decades. This paper illustrates the financial evaluation of a M&A activity. By using the Discount Cash Flow (DCF) method and Market Multiple model, it demonstrates and expresses the value differing from the assumptions and conditions that are adopted in the calculation. Meanwhile, through the specific case study of BenQ’s failure to takeover Siemens Mobile Division in handset industry, it brings an argument that is significant in its own right, but is also a mixture of diverse issues involving financial evaluation, culture management in cross-broad circumstance, shareholder value maximisation and agency problem as well. Moreover, the objective of this paper is to stress on the evaluation on the target company during the pre-acquisition period, which requires careful due diligence to minimise potential risks and errors in value prediction in the beginning. Meanwhile, it also points out that the success of post-acquisition integration is highly relevant to the management strategy, but a failure to conduct it could lead to synergy that is not produced as early as expected and continuing operation expenditures that can cause a severe financial burden to the acquirer, which will change its capital structure and undermine its competition and business capability on the market as well. The focus on the M&A case of BenQ merge with Siemens implicates relevant topics, including the conflict between corporate social responsibility (CSR) and shareholder value maximisation. In addition, the interrelation between investment bank and enterprises involved in the M&A activities with the possible conflict against shareholder due to the concern of agency problem results in the inappropriate investment. Finally, it concludes that the future projection needs to be made on the basis of every aspect in business world; financial evaluation cannot be the singular element to accomplish successful M&A unless supported by all other strategic fits in operation.